Prediction models for bank failure: ASEAN countries - Anggraeni, Anggraeni; Abdul Mongid,; Suhartono, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The paper analyses how global financial crisis effects the performance of banks. This study further estimate the determinants of banks failure on a sample of banks in ASEAN countries namely, Indonesia, Malaysia, Singapore, Cambodia, Thailand, Philippine, Singapore, and Vietnam. We define a bank as having failed when its profitability, equity, and loan quality are below a minimum standard. Besides bank-specific variables (microeconomic variables), some macroeconomic variables have been considered in this study. The findings reveal that during global finance crisis, the performance of the banks is at its weakest before its significant recovery. The findings show that the banking failure is positively linked to cost inefficiency, debt to equity ratio, an inflation rate, but negatively related to profitability. The findings suggest that cost inefficiency, can serve as a foundation for corrective action to be considered by banking authorities in the future.